Characterisation of the Cenozoic volcanism in northern Peru (7°45'9° QQ's; 78°QQ'-78°45'w) - Rivera Porras, Marco Antonio (2005)
ln northern Peru, along Andean Cordillera outcropping volcanic and volcanoclastics deposits of ~3000 m thick, emplaced during the subaerial volcanism occurred between 53 - 14,6 Ma. (Wilson, 1975; Farrar & Noble, 1976), it is in the Eocene-Miocene. Cossio (1964) named this volcanism as Calipuy Formation, later the term Calipuy Group was used by Cobbing (1973) to refer ail the Cenozoic volcanic rocks in northern Pern. Volcanic studies made in a sector of northern Pern (Figure 1), show the existence of eight eroded volcanoes, two collapse calderas, domes, as weil as pyroclastics sequences, lava flows and lahars, emplaced during the intense volcanism occurred in Eocene-Miocène. Most of the volcanic centres had an evolution phase, characterized at the beginning by effu sive eruptions that emplaced lava flows interbedded with pyroclastic fIow deposits and lahars, and a final phase generally explosive characterized by emissions of important volumes of pyroclastics flows and lahars. Generally, the volcanic centres were built along NW-SE trending fractures and regional faults. The generation of the Cenozoic volcanisrn is possibly bounded to the mechanism of Nasca Plate subduction that generated the partial melting of the mantle wedge (Werner, 1991).